Application of phiC31 integrase system in stem cells biology and technology: a review. Issue 1 (1st January 2018) - Fani Maleki, Adham; Sekhavati, Mohammad Hadi
ABSTRACT: Two specific characteristics of stem cells, self-renewal and their differentiation capacity have made them important for vast scientific areas, particularly in the molecular and cell biology of stem cells, as well as regenerative medicine. Gene targeting plays a pivotal role in creating modified stem cells, which are considered the mainstay in regenerative medicine. The phiC31 integrase system, as a site-specific recombinase, could be a straightforward and efficient approach for this aim. According to the high potential of the application of phiC31 integrase system in stem cells, the present paper reviews previous studies, placing the focus on stem cell types and their application.